Comparative analysis of current and voltage-controlled photovoltaic Maximum Power Point tracking - De Assis Sobreira, Pedro; Villalva, Marcelo Gradella [UNESP]; Barbosa, Pedro Gomes; Braga, Henrique Antônio Carvalho; Gazoli, Jonas Rafael; Ruppert, Ernesto; Ferreira, André Augusto (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Maximum Power Point tracking (MPPT) in photovoltaic (PV) systems may be achieved by controlling either the voltage or current of the PV device. There is no consensus in the technical literature about how is the best choice. This paper provides a comparative analysis performance among current and voltage control using two different MPPT strategies: the perturb and observe (P&O) and the incremental conductance techniques. © 2011 IEEE.
Keywords: current control; maximum power point tracking; MPPT; photovoltaic system; voltage control; Best choice; Comparative analysis; Incremental conductance; Perturb and observe; Photovoltaic systems; Technical literature; Voltage-controlled; Electric current control; Power electronics; Voltage control; Photovoltaic effects